Gas production characteristics of biogenic gas simulated in hydrate-developing area of Dongsha area, South China Sea - Su, Pibo; Wei, Wei; Shi, Chaoqi; Li, Jin; Han, Weifeng; Xiao, Zebang; Liang, Jinqiang; Wang, Feifei; Wan, Zhifeng (Frontiers in Marine Science, 2023)
Most of the natural gas hydrate sources in the world are biogenic gas, but there are still many unsolved problems in the formation process of biogenic gas. The gas source of gas hydrates in the northern South China Sea is also controversial, and the evaluation of biogas source rock in hydrate development areas lacks experimental basis and quantitative data. In order to solve these problems, this paper used the sediments obtained from the GMGS2 hydrate drilling voyage to simulate the biological gas production. Through the culture experiment, the relationship between sedimentary gas production, temperature and sediment characteristics in the hydrate development area of Dongsha Sea area was comparatively studied, and the results were compared with typical biological gas fields. The results showed that CH4 and CO2 were the main gas products, and a small amount of H2 was formed. Methane yield is closely related to temperature, and the optimal temperature range in the study area is 20°C~ 40°C. At the same time, it is found that organic carbon content (TOC) has no significant correlation with methane yield, and it is not suitable to be used as an index for the evaluation of biogas source rock. Comprehensive analysis shows that the methane production rate in the study area is relatively high and the hydrocarbon generation potential is great, which meets the gas source conditions for the formation of gas hydrate ore body. The main factors affecting biomethane yield include available organic matter, bacterial community and environmental factors.